Virologic and Immunologic Characteristics in Mature Ducks with Acute Duck Hepatitis A Virus 1 Infection - Mao, Sai (Front Immunol, 2017)
Duck hepatitis A virus 1 (DHAV-1) infection in mature ducks has previously been proposed as a small-animal model for human hepatitis A. However, basic research on the outcome of DHAV-1 infection in mature ducks is limited. Here, we examined the course of viremia, the characteristics of antibody responses, and the profiles of plasma cytokines in mature ducks infected with DHAV-1. During the course of infection, the viremia was detectable soon after infection and persisted for 196 days, however, the ducks presented as clinically asymptomatic. Specific and timely immunoglobulin G (IgG), IgM, and IgA1 responses were elicited. At the same time, extensive inhibition of viral replication was observed with increasing IgG concentration. With respect to pattern-recognition receptors, TLR-7 was mainly involved in triggering the innate defense against the DHAV-1 infection. In addition, plasma immune analytes were measured and were determined to have bidirectional roles in virus clearance. It was concluded that DHAV-1 spreads quickly in blood. The spontaneous clearance of DHAV-1 during asymptomatic infection in mature ducks depends on the cooperation of timely antibody responses and alert innate immune responses. Moreover, the delayed clearance may be associated with a weak interferon-γ-producing CD8+ T cell response. This study allows us to reveal the mechanism of clearance and persistence of DHAV-1 infection in mature ducks. We anticipate that it will provide a basis for future studies focused on defining the nature mechanisms involved in the clearance and persistence of human hepatitis virus.